2014
DOI: 10.3109/03630269.2013.869501
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Outcome of Women With Sickle Cell Disease of a Tribal Population in Central India

Abstract: Pregnancy in sickle cell disease is associated with increased risk of maternal and fetal morbidity and mortality. Sickle cell disease is very common in tribal populations. The objective of this study was to review the maternal and perinatal outcome in patients with sickle cell disease of tribal populations. This is a retrospective study. The data extracted from the patients' case files included age, gravidity, family history, complications during pregnancy or at time of delivery or postpartum period, mode of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…[24][25][26][27][28][29][30][31] All studies were categorized as pregnancy cohort studies. Thirteen studies originated For personal use only.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31] All studies were categorized as pregnancy cohort studies. Thirteen studies originated For personal use only.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Women with pre-eclampsia also have a reduced plasma volume at the time of diagnosis and associated intrauterine growth restriction; under-activity of the RAAS has been found in such women as well. 17 , 18 Pregnant HbSS women have been reported to have a higher incidence of pre-eclampsia 19 - 22 although not all studies have found this association. 4 , 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…There were 25 deliveries to women with sickle cell disease and preeclampsia and disseminated intravascular coagulation were common problems. There was no maternal mortality; however, there were five intrauterine foetal deaths and one early neonatal death 50 .…”
Section: Clinical Presentation and Care Of Sickle Cell Disease Cases mentioning
confidence: 86%